(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate the influence of Orthoptic exercise on near point of converge in patients with Convergence insufficiency (CI). Study Design: Interventional longitudinal study Place and Duration of Study: This study was conducted at the Eye Clinic of Al-Ibrahim Eye hospital Karachi for a period of 8 months October 2020 to April 2021. Materials and Methods: 60 patients with confirmed diagnoses of CI were chosen for the study. All of the patients were prescribed pencil push-up tests as a form of Orthoptic Exercise to reduce CI. The pre and post Near Point of Convergence was determined and compared using the chi-square test with P-value ≤0.05 considered being statistically significant. Results: Significant difference (P-value ≤0.001) was seen in Pre and Post Near Point of Convergence in the group without glasses and the group with glasses. Conclusion: Orthoptic Exercises proved to be influential in improving the Near point of Convergence